Effect of position, time in the season, and playing surface on Achilles tendon ruptures in NFL games: a 2009-10 to 2016-17 review - Krill, M. K.; Borchers, J. R.; Hoffman, J. T.; Krill, M. L.; Hewett, T. E. (The Physician and Sportsmedicine, 2017)
Objectives: Achilles tendon (AT) ruptures are a potentially career-altering and ending injury. Achilles tendon ruptures have a below average return-to-play rate compared to other common orthopaedic procedures for National Football League (NFL) players. The objective of this study was to monitor the incidence and injury rates (IR) of AT ruptures that occurred during the regular season in order to evaluate the influence of player position, time of injury, and playing surface on rupture rates.